Epistemological Analysis and Pedagogical Challenges of Tafsīr al-Jalālayn Instruction at Dayah Istiqamatuddin Darul Mu’arrif Aceh Besar - Rahmadi, Farhan; Latif, Lazuardi Muhammad; Rizki, Aulia (TAFSE: Journal of Qur'anic Studies, 2026)
This study investigates the epistemological structure and pedagogical challenges of tafsīr instruction at Dayah Istiqamatuddin Darul Mu’arrif, Aceh Besar. The research addresses the problem of epistemic limitation resulting from the exclusive reliance on Tafsīr al-Jalālayn and its commentary, Ḥāshiyah al-Ṣāwī, within the tafsīr curriculum of the dayah. This study specifically asks how the use of a single authoritative text influences students’ interpretive competence and the formation of contemporary mufassirīn in the context of modern Qur’anic studies. Employing a qualitative phenomenological approach, data were collected through observation and in-depth interviews with seven purposively selected informants consisting of dayah leaders, teachers, and students. The findings reveal that traditional pedagogical methods such as talaqqī and tikrār strengthen sanad-based knowledge transmission and preserve traditional scholarly authority. However, the exclusive dependence on a single tafsīr text limits students’ comparative hermeneutical perspectives, restricts methodological exploration, and contributes to the restriction of interpretive agency. The study further identifies limited instructional time, restricted access to broader references, and the absence of independent instruction in ‘ulūm al-tafsīr as significant obstacles in developing critical interpretive competence. This study concludes that curriculum reconstruction through the integration of comparative tafsīr studies and broader access to scholarly resources is necessary to balance the preservation of traditional Islamic scholarship with the demands of contemporary analytical and contextual Qur’anic interpretation.